In Vitro and In Vivo Antimetastatic Effect of Glutathione Disulfide Liposomes. (6th March 2017) - Sadhu, Satya S; Wang, Shenggang; Dachineni, Rakesh; Averineni, Ranjith Kumar; Seefeldt, Teresa; Xie, Jiashu; Tummala, Hemachand; Bhat, G Jayarama; Guan, Xiangming
Cancer metastasis is the major cause of cancer mortality. Despite extensive research efforts, effective treatment for cancer metastasis is still lacking. Cancer metastasis involves 4 essential steps: cell detachment, migration, invasion, and adhesion. Detachment is the first and required step for metastasis. Glutathione disulfide (GSSG) is derived from the oxidation of glutathione (GSH), which is present in biological systems in millimolar concentration. Although GSSG is commercially available, the impact of GSSG on cell functions/dysfunctions has not been fully explored due to the fact that GSSG is not cell membrane permeable and a lack of method to specifically increase GSSG in cells. We have developed GSSG liposomes that effectively deliver GSSG to cells. Unexpectedly, cells treated with GSSG liposomes were resistant to detachment by trypsinization. This observation led to the investigation of the antimetastatic effect of GSSG liposomes. Our data demonstrate that GSSG liposomes at 1 mg/mL completely blocked cell detachment and migration, and significantly inhibited cancer cell invasion. Aqueous GSSG showed no such effect, confirming that the effects on cell detachment, migration, and invasion were caused by the intracellular delivery of GSSG. An in vivo experiment with a murine melanoma experimental metastasis model showed that GSSG liposomes prevented melanoma lung metastasis. The unique antimetastatic mechanism through the effects on detachment and migration, and effective in vitro and in vivo metastasis inhibition, warrants further investigation of the GSSG liposomes as a potential treatment for cancer metastasis.